The Food and Feeding Habits of the Common Bay Anchovy, Anchoa Mitchilli (Valenciennes) - Din, Zubir; Gunter, Gordon (1986)
The food and feeding habits of Anchoa mitchilli studied at three stations in the Biloxi Bay area, Miss~stppi. Studies on the behavioural aspects offeeding were designed to include a 24-hour observation of a feeding rhythm. Results of the study indicated that the bay anchovy in this area Jed mainly during early morning with a second, minor peak, just before midnight. The anchovy appeared to be dependent on both plankton and benthic organisms for food. Crustaceans were the main food items consumed, with calanoid copepods being the most prominent, numerically. Cannibalzstic behaviour was identified, and this coincided with periods of low abundance of other food items. Different feeding methods were employed by the fish for various feeding situations. Small plankton were filtered through the water column, while larger organzsms were picked individually. When the situation demands, the anchovy will also prey actively on its food.